Do the humanities have a future? - Quiroz Ávila, Rubén (2024)
Our argument has an inherent bias. That is to say, we come from the humanities, we have been educated around it, and, of course, it is evident that there is a much greater probability that we will defend its value. This foundation has several possible dimensions. Perhaps the most important appeals to its inherently ethical condition and the profound system of self-reflection and cautious criticism that characterizes it. It is also true that the current job horizons are not necessarily favorable for it to be a solid argument. Moreover, for such a vigilant model of knowledge, it is seen as a destabilizing space.